Psychiatric morbidity in epilepsy: a case controlled study of adults receiving disability benefits. Issue 2 (1st February 1998) - Stefansson, Sigurjon B; Olafsson, Elias; Hauser, W Allen
Abstract : OBJECTIVE: To compare the prevalence of non-organic psychiatric disorders among disabled patients of normal intelligence with epilepsy with the prevalence of similar psychiatric disorders among age and sex matched disabled patients with other somatic diseases. METHODS: A case-control study was carried out in Iceland among people receiving disability benefits using information available at the State Social Security Institute. There were 344 patients with epilepsy in Iceland 16 to 66 years of age (inclusive) receiving disability benefits in 1995. By excluding mentally retarded patients, autistic patients, and patients with organic psychoses, 241 index cases with epilepsy qualified for the study. For each case two age and sex matched controls were selected from all patients receiving disability benefits who had cardiovascular diseases, respiratory diseases, or arthropathies. The same exclusion criteria were applied to the controls as the index cases. In both patient groups psychiatric diagnoses were classified into one of the four following categories: (1) psychotic illness; (2) neurotic illness or personality disorders; (3) alcohol or drug dependence or misuse; and (4) other mental disorders. RESULTS: Psychiatric diagnosis was present among 35% ( 85/241) of the cases compared with 30% (143/482) of the controls (p=0.15). There was a difference in the distribution of the two groups into different psychiatric categories (p=0.02). This was mainly due to an excess of men in the index group with psychosis, particularly schizophrenia or paranoid states. CONCLUSION: The results suggest that there is not a difference in the prevalence of non-organic psychiatric disorders among disabled patients of normal intelligence with epilepsy compared with patients with other disabling somatic diseases. However, the data indicate that when psychopathology is present disabled patients with epilepsy are more likely to have psychotic illness than the other disabled patients.